Analisis Manajemen Pelayanan Publik Dalam Meningkatkan Minat Baca Masyarakat (Studi Pada Kantor Perpustakaan Daerah Kabupaten Kolaka Utara) - Firdayanti, Firdayanti; Utha, Arifin; Tawai, Adrian (REZ PUBLICA, 2020)
This Research Aims To Know How Public Service Management In Increasing Public Reading Interest In The Library Office Of North Kolaka Regency. The Method Used In This Research Is To Use A Descriptive Qualitative Approach By Means Of Observation, Interview And Documentation. Based On The Results Of Research Conducted By Researchers Regarding Public Service Management In Increasing Public Reading Interest, It Can Be Concluded That Public Service Management In Increasing Public Reading Interest Carried Out By The Library Has Not Been Fully Maximized. Given That There Are Still Shortcomings Of Interview Results From The Library And From The Library User Community. Where The Facilities And Infrastructure Owned By The Library Are Not Completely Adequate. Service Fees Also That Do Not Have Written Rules. Then Regarding Reading Gardens Cannot Be Realized Well. Also For The Promotion Has Not Been Going Well Because In Its Implementation, The Library Has Not Fully Involved Community Leaders. In Addition, Reading Activities Have Not Gone Well, Because The Library Has Not Fully Involved All Related Elements.